Irrational Ideation and its Connection to the view point of Taking Risks Within Prisoners In The Erbil Governorate Center (Raparin Journal of Humanities (RJH), 2024)
Irrational thoughts and risk-taking tendencies are a serious problem. When a person has these traits or behaviors, it can lead to the destruction of the individual, as well as the collapse of society and its lack of development. These traits can also have a negative impact on other individuals, especially children and adolescents.The current study aimed to examine the level of irrational thoughts and risk-taking tendencies among prisoners, as well as the relationship between these two variables. The study sample consisted of 154 male and female prisoners.The results showed that the prisoners did not have high levels of irrational thoughts. However, they did have a moderate level of risk-taking tendencies. There was no significant difference in the level of irrational thoughts or risk-taking tendencies between males and females. There was also no significant difference in the level of these two variables according to age.The results of the study suggest that prisoners may be more likely to engage in risky behaviors than the general population. However, it is important to note that the study sample was relatively small, and further research is needed to confirm these findings.